Faktor-Faktor Penyebab Adanya Dugaan Praktek Kartel Harga Minyak Goreng di Indonesia - Ananda Nugraha; Rahmi Zubaedah; Rani Apriani (Jurnal Ilmiah Wahana Pendidikan, 2022)
The practice of cooking oil price cartel activities based on Pasal 11 UU No. 5 1999, based on this pasal business actors are explicitly prohibited from entering into agreements with competing business actors for the purpose of regulating the production, marketing of goods and / or services. However, in their activities, cooking oil business actors have been suspected of carrying out activities on the practice of cooking oil price cartels in Indonesia. So the purpose of this study is to find out and understand what factors are the alleged practices of price cartels in cooking oil in Indonesia. The method used in this study, using the normative juridical method, based on this method the researcher conducted research by examining library materials in the form of secondary data or legal research with literature studies related to the alleged practice of cartels of cooking oil prices in Indonesia. The proof of alleged cartel practices with the principles of rule of reason and indirect evidence is still not regulated in the laws and regulations, it should be that the existence of the principle of rule of reason and indirect evidence needs to be considered more deeply in solving alleged cartel practices in Indonesia.